Upaya Pengentasan Kemiskinan Melalui Program Keluarga Harapan di Nagari Balimbing - VICY ANDRIANY, M.Ec.Dev ANDRIANY (UIN Mahmud Yunus Batusangkar, 2021)
This study aims to determine the role of the Family Hope Program in poverty alleviation in Nagari Balimbing. The problem in this study is seen from the poverty rate which is still quite high in Nagari Balimbing.The type of research carried out isfield researchwith qualitative descriptive research methods, data collection techniques used in this study are observation, interviews, and documentation.From the research the author conducted in the field, it can be concluded that the role of the Family Hope Program (PKH) in alleviating poverty in Nagari Balimbing, Rambatan District, Tanah Datar Regency shows that PKH can gradually reduce poverty in Nagari Balimbing, which is evidenced by the existence of people who self-graduation or KPM which ends in PKH KPM membership, due to improved socio-economic conditions. In terms of education, poor people who receive PKH assistance can improve education for their children and from a health perspective, their condition can be monitored for pregnant women and toddlers can grow up healthy and smart because their growth and development can be consulted at the posyandu.